Comparing Diet and Exercise Monitoring Using Smartphone App and Paper Diary: A Two-Phase Intervention Study - Jimoh, Florence; Lund, Elizabeth K; Harvey, Linda J; Frost, Catherine; Lay, W James; Roe, Mark A; Berry, Rachel; Finglas, Paul M (JMIR Publications, 2018)
BackgroundThere is increasing recognition that personalized approaches may be more effective in helping people establish healthier eating patterns and exercise more, and that this approach may be particularly effective in adolescents. ObjectiveThe objective of this study was to investigate the use of a smartphone app (FoodWiz2) in supporting healthy lifestyle choices in adolescence. MethodsParticipants (N=34: 11 male, 23 female) aged 16-19 years in full- or part-time education were recruited from sixth form colleges, schools, and other further education establishments in Norfolk and Suffolk, United Kingdom, between February and May 2015. Participants recorded food intake and exercise using a paper diary for 4-5 weeks and then used the app for the same duration. Initial nutrition education and general support were provided during the paper diary use, but the app included personalized messages sent in response to app activity. At the end of each study phase, participants completed an online questionnaire to describe their experience of using the paper diary and app. ResultsRecord completion declined throughout the study, possibly affected by examination pressure. Food intake data showed increased fruit consumption and significantly reduced consumption of chocolate snacks (P=.01) and fizzy drinks (P=.002) among participants using the app. Questionnaire responses indicated that the app was generally preferred to the paper diary, in particular, the app was seen as less boring to use (P=.03) and more acceptable in social settings (P<.001). ConclusionsThis app-based approach has shown the potential for a more effective approach to improving adolescent diet and exercise levels.